A Potential circRNA-miRNA-mRNA Regulatory Network in Asthmatic Airway Epithelial Cells Identified by Integrated Analysis of Microarray Datasets - Chen, Dian; Wu, Wenliang; Yi, Lingling; Feng, Yuchen; Chang, Chenli; Chen, Shengchong; Gao, Jiali; Chen, Gongqi; Zhen, Guohua (Frontiers in Molecular Biosciences, 2021)
Abstract Background: Asthma is one of the most prevalent chronic respiratory diseases worldwide. Bronchial epithelial cells play a critical role in the pathogenesis of asthma. Circular RNAs (circRNAs) act as microRNA (miRNA) sponges to regulate downstream gene expression. However, the role of epithelial circRNAs in asthma remains to be investigated. This study aims to explore the potential circRNA-miRNA-mRNA regulatory network in asthma by integrated analysis of publicly available microarray datasets. Methods: Five mRNA microarray datasets derived from bronchial brushing samples from asthma patients and control subjects were downloaded from the Gene Expression Omnibus (GEO) database. The robust rank aggregation (RRA) method was used to identify robust differentially expressed genes (DEGs) in bronchial epithelial cells between asthma patients and controls. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were used to annotate the functions of the DEGs. Protein-protein interaction (PPI) analysis was conducted to identify hub genes. Three miRNA databases (Targetscan, miRDB, and miRWalk) were used to predict the miRNAs which potentially target the hub genes. A miRNA microarray dataset derived from bronchial brushings was used to validate the miRNA-mRNA relationships. Finally, a circRNA-miRNA-mRNA network was constructed via the ENCORI database. Results: A total of 127 robust differentially expressed genes (DEGs) in bronchial epithelial cells between steroid-naïve asthma patients (n = 272) and healthy controls (n = 165) were identified from 5 mRNA microarray datasets. Enrichment analyses showed that DEGs were mainly enriched in several biological processes related to asthma, including humoral immune response, salivary secretion, and IL-17 signaling pathway. Nineteen hub genes were used to construct a circRNA-miRNA-mRNA network. The top 10 competing endogenous RNAs were hsa_circ_0001585, hsa_circ_0078031, hsa_circ_0000552, hsa-miR-30a-3p, hsa-miR-30d-3p, KIT, CD69, ADRA2A, BPIFA1, and GGH. Conclusion: Our study reveals a potential role for epithelial circRNA-miRNA-mRNA network in the pathogenesis of asthma.